INQUIRY LEARNING: A METHOD TO TEACH SPEAKING FOR THE TENTH GRADE STUDENTS - Bahrinda Eka Putri; wiki tedi rahmawati; Linda Astuti Rangkuti (EXCELLENCE: Journal of English and English Education, 2022)
The objective of this research was to find out the effect of using inquiry learning method on students’ ability in speaking. This research was conducted at SMK Abdi Negara Binjai. The population of this research was the tenth grade students in academic year 2021-2022. There were 2 classes consisting of 55 students. The sample with total number of 20 students were taken by using random sampling with lottery technique. The sample was divided into 2 groups. Experimental group consisted of 10 students was taught using inquiry learning method and control group consisted of 10 students was taught using conventional method. The instrument for collecting the data was a speaking test. Each group was given a pre-test, treatment, and post-test. The result of this research showed that the mean of post-test in experimental group (51.6) was higher than control group (44.2) and the value of U-observed (25) was smaller than the value of U-table (30). The testing of hypothesis showed that Ho was rejected and Ha was accepted. It meant that there was a significant effect on students’ speaking ability taught by using inquiry learning method.